Receptor-based 3D-QSAR approach to find selectivity features of flexible similar binding sites: case study on MMP-12/MMP-13 - Hadizadeh, Farzin; Shamsara, Jamal (International journal of bioinformatics research and applications, 2015)
Design of selective matrix metalloproteinases (MMPs) inhibitors is still a challenging task because of binding pocket similarities and flexibility among MMPs family. To overcome this issue we try to generate a (three-dimensional quantitative structure activity relationship) 3D-QSAR model that might reflect, at least in part, the differential properties of MMP-12 and MMP-13 active sites compared to each other. The different alignment rules were applied for CoMFA/CoMSIA model development. In an approach the best docked poses were followed by alignment based on their zinc binding group. As it was suggested by comparison of CoMSIA contour maps of MMP-12 with MMP-13, the ligand based approach can find more detailed features of specificity for MMPs that have similar highly flexible active sites, than solely analysis of available crystal structures. The residues Val(194), Leu(214) and Thr(220) of MMP-13 were suggested to be investigated for flexibility upon binding of different ligands.